2022
DOI: 10.1039/d1tb02415a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced immobilization of 2-methacryloyloxyethyl phosphorylcholine polymers with different molecular architectures on a poly(ether ether ketone) surface

Abstract: Poly(ether ether ketone) (PEEK) has seen increasing use in biomedical fields as a replacement for metal implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Poly(ether-ether-ketone) (PEEK) is regarded as an ideal material for bone repair owing to its good biocompatibility, excellent mechanical properties, and bone-like stiffness. 12,13 In addition, PEEK is also known to significantly reduce CT artifacts and improve image quality facilitating the radiological interpretation of implant surrounding tissues, which lead to the increasing use of PEEK implants for the repair of cranial defects. 14 Rosenthal et al 14 reported 66 cases of PEEK cranioplasty with comparable complications to the autologous bone; Hanasono et al 15 reported 6 cases in which PEEK implants were used to repair large cranial defects without complications.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ether-ether-ketone) (PEEK) is regarded as an ideal material for bone repair owing to its good biocompatibility, excellent mechanical properties, and bone-like stiffness. 12,13 In addition, PEEK is also known to significantly reduce CT artifacts and improve image quality facilitating the radiological interpretation of implant surrounding tissues, which lead to the increasing use of PEEK implants for the repair of cranial defects. 14 Rosenthal et al 14 reported 66 cases of PEEK cranioplasty with comparable complications to the autologous bone; Hanasono et al 15 reported 6 cases in which PEEK implants were used to repair large cranial defects without complications.…”
Section: Introductionmentioning
confidence: 99%